How does the length of time in the emergency department to achieve the therapeutic goals in patients with severe sepsis or septic shock affect the in-hospital all-cause mortality rate? - Tangsuwanaruk, Theerapon; Wittayachamnankul, Borwon; Chenthanakij, Boriboon (Biomedical Sciences and Clinical Medicine, 2018)
Objective To assess the correlation between duration to achieve therapeutic goals in Early goal-directed therapy (EGDT) protocol in emergency department (ED) for severe sepsis or septic shock patients and in-hospital all-cause mortality as primary outcome. Methods A retrospective descriptive study was conducted in ED, Maharaj Nakorn Chiang Mai Hospital between June 1, 2011 and December 31, 2014. Patients with severe sepsis or septic shock were treated according to EGDT protocol to achieve therapeutic goals in ED. The correlation between duration to achieve therapeutic goals and in-hospital all-cause mortality was analyzed by logistic regression model. Results One hundred and seven patients were enrolled. In-hospital all-cause mortality was not related to duration to achieve therapeutic goals in ED (regression coeffi cient -0.01;p=0.11). Critical care length of stay (LOS) (Spearman rank correlation coefficient; rs; -0.14;p=0.14), overall LOS (rs 0.03; p=0.73), critical care free days (rs 0.10; p=0.32), number of antibiotics used (rs 0.01; p=0.91), antibiotic free days (rs -0.02; p=0.81), and complications (regression coefficient -0.01 to 0; p >0.05) were not related to duration to achieve therapeutic goals in ED. Conclusions Duration to achieve therapeutic goals may not be related to the in-hospital all-cause mortality in patients with severe sepsis or septic shock within the first hours in ED. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />